FORMULASI DAN EVALUASI STABILITAS TIGA SEDIAAN HERBAL CAIR: SIRUP POLIHERBAL, FOOT SANITIZER, DAN FACE SPRAY - Dhiya Shoufi Sahaja; Aura Nasyafa; Nor Latifah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study presents an in-depth review of three journals focusing on the formulation, evaluation, and stability of polyherbal syrup preparations containing extracts of Moringa oleifera (drumstick leaves), Curcuma longa (turmeric rhizome), and Zingiber officinale (ginger rhizome). The polyherbal syrup is known for its strong antioxidant activity, with potential benefits as an immunomodulator and protection against degenerative diseases. The primary study emphasized physical stability testing through accelerated stability studies at 40°C ± 2°C and 75% ± 5% relative humidity for three months, using three preservative variations: sodium benzoate, methylparaben, and propylparaben. Evaluation of organoleptic properties, pH, viscosity, and specific gravity revealed that all formulations maintained good physical stability throughout the testing period. The review also highlights the importance of standardizing herbal raw materials through organoleptic testing, moisture content, water-soluble extract, and ethanol-soluble extract measurements to ensure consistent product quality. The syrup production process involves aqueous extraction of the herbal materials, followed by formulation with additional ingredients such as palm sugar, tamarind, lime, and appropriate preservatives. Overall, the findings suggest that this polyherbal syrup has significant potential as a stable, safe, and effective phytopharmaceutical product, supporting the utilization of local natural resources for the development of competitive herbal medicines in the modern pharmaceutical market.